1997
DOI: 10.1007/pl00006196
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the intergenic region of the duplicated amy genes of drosophila melanogaster and drosophila teissieri

Abstract: The intergenic regions between the duplicated amylase coding regions (Amy) of D. melanogaster and D. teissieri were sequenced. Their lengths in D. melanogaster and D. teissieri were 4,536 bp and 4,621 bp, respectively. Since homology between the upstream regions of the two duplicated genes was found up to 450 bp from the initiation codon of the Amy genes, the ancestral Amy coding region duplicated together with at least 450 bp of the 5'-flanking region as one unit. Comparison of the regions between the two spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Only one has been well characterized as a cloned protein . Another has been identified as a gene encoding an active serpin, and the presence of one has been inferred from its ability to form a higher molecular weight covalent complex with the serine proteinase Easter . A study aimed at identifying proteins produced by the male accessory gland and secreted into seminal fluid identified 12 such proteins, one of which (Acp76A) was a serpin (orphan) …”
Section: 5 Drosophila and Other Arthropod Serpinsmentioning
confidence: 99%
“…Only one has been well characterized as a cloned protein . Another has been identified as a gene encoding an active serpin, and the presence of one has been inferred from its ability to form a higher molecular weight covalent complex with the serine proteinase Easter . A study aimed at identifying proteins produced by the male accessory gland and secreted into seminal fluid identified 12 such proteins, one of which (Acp76A) was a serpin (orphan) …”
Section: 5 Drosophila and Other Arthropod Serpinsmentioning
confidence: 99%
“…Thus, it was found that the expressed, functional Supt4h2 gene was created by reintegration of a processed mRNA transcript of the Supt4h gene on a different chromosome, under the control of a new, previously unrelated promoter. Likewise, the extremely high degree of intraspecific sequence conservation of an intergenic region (>1000 bp) between two copies of duplicated amylase genes within the Drosophila species complex is due to another functional gene which is encoded by the conserved area (Okuyama et al 1997).…”
Section: Discussionmentioning
confidence: 99%